Superhard composites of cubic silicon nitride and diamond - Wang, Wendan; He, Duanwei; Tang, Mingjun; Li, Fengjiao; Liu, Lei; Bi, Yan (Diamond and related materials, 2012)
Powder mixture of graphite and silicon nitride with hexagonal structure (α/β-Si3N4) was ball-milled in nitrogen and compressed under ~16GPa/1800°C and ~18GPa/2000°C, to investigate the possibility for replacing Si atoms by C atoms in cubic spinel silicon nitride (c-Si3N4). The sintered samples were characterized by X-ray diffraction (XRD), hardness measurement, optical microscope, scanning electron microscopy (SEM) and high-resolution transmission electron microscopy (HRTEM). The results show that the well-sintered compacts were composed of nanocrystalline c-Si3N4 and nanocrystalline diamond, and neither C3N4 and CSi2N4 nor other reaction products of Si3N4 and C were observed. Vickers hardness test shows that the average hardness of the samples is 41–42GPa. As a comparison, phase-pure c-Si3N4 bulks also have been synthesized and their hardness was confirmed to be about 31GPa. The pure c-Si3N4 sintered bulks exhibit a high frangibility, but their fracture toughness could be largely improved by adding carbon (nanocrystalline diamond) in the sintered compacts. ► Well-sintered compacts of c-Si3N4 and diamond composite have been synthesized. ► Nanodiamond improved the sintered compacts in hardness and fracture toughness. ► Vickers hardness of c-Si3N4 was confirmed to be 31GPa by synthesized pure bulks. ► Si atoms in Si3N4 cannot be replaced by C atoms up to 18GPa and 2000°C.